Facile preparation of uniform polydopamine particles and its application as an environmentally friendly flame retardant for biodegradable polylactic acid. (November 2020) - Tawiah, Benjamin; Yu, Bin; Yuen, Anthony Chun Yin; Fei, Bin
The demand for environmentally benign flame retardants for biodegradable polymers has become particularly necessary due to their inherently "green" nature. This work reports intrinsically non-toxic polydopamine (PDA) particles as an efficient and environmentally friendly flame retardant for polylactic acid (PLA). 5 wt% PDA loading resulted in a 22% reduction in the peak heat release rate, 34.7% increase in the fire performance index, and lower CO2 production compared to neat PLA. A limiting oxygen index (LOI) value of 27.5% and a V-2 rating was achieved in the UL-94 vertical burning test. Highly aggregated amorphous particulate char was formed with the increasing content of PDA, and a significant reduction in evolved pyrolysis gaseous products was achieved for the PLA/PDA composites as compared with control PLA. This work provides important insight into the potential commercial application of PDA alone as an efficiently green, environmentally benign flame retardant for bioplastic PLA.